O ensino do Português Língua Não Materna. Perceções e práticas de integração em cinco escolas de São Miguel - Açores (Revista Lusófona de Educação, 2026)
Abstract: This year, 2025, marks two decades since the formal introduction of Portuguese as a Non-Native Language (PLNM) into the Portuguese education system. During this period, remarkable progress has been made, not only in terms of published legislation, monitoring of attendance, teaching and results of the course unit, but also in terms of the experience gained by schools and their teachers in welcoming and working with students. However, there is one aspect that remains completely unchanged in this area, namely professional qualification for teaching this specific subject. In the qualitative study we present, based on interviews with Portuguese teachers in the Autonomous Region of the Azores, which aims to obtain a picture of the integration of migrant students in public schools in São Miguel from the teachers' point of view, the results generally point to a very positive assessment of the work in progress, but it is precisely the lack of training in the subject area that is the main complaint mentioned.